PENGARUH SERVICE QUALITY, BRAND IMAGE, BRAND EQUITY DAN CORPORATE REBRANDING TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA TRANSMART INDONESIA - Sularso, Raden Andi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This study analyzes the effect of service quality, brand image, brand equity, and corporate rebranding on customer satisfaction and loyalty of Transmart. The sample consisted of 200 respondents taken using the random sampling technique. Data were analyzed using Structural Equation Modeling. The results prove that service quality, brand image, and brand equity affect customer satisfaction and loyalty of Transmart. Corporate rebranding has a direct effect on customer satisfaction but does not affect the customer loyalty of Transmart. Keywords: brand equity, brand image, corporate rebranding, service quality